Breeding Grain Sorghum for Tolerance to Aluminium Toxicity - Too, E. J.; Gudu, S.; Were, B. A.; Onkware, A. O. (Africa Environmental Review Journal, 2020)
Aluminium (Al) toxicity is a common problem in acid soils where sorghum (Sorghum bicolor (L.) Moench) is grown. It contributes to grain yield reduction of between 30-40 % in sorghum and other cereals. Al interferes with plant development by inhibiting root growth, thus contributing to reduced uptake of water and mineral nutrients. The main aim of this study was to transfer Al tolerance to a local farmer preferred commercial variety. The specific objectives of the study were to (i) assess aluminium stress response of F2 sorghum segregating populations derived from a cross between Seredo and ICSR 110 together with the parental lines and the F1 hybrid in solution culture and (ii) to assess growth and production of the same panel of sorghum genotypes when grown in acidic soils with and without application of lime. A cross was made between Seredo (Al-sensitive commercial variety) and ICSR 110 (Al-resistant line). In the laboratory, seedlings of F1s and F2s and the parental lines were grown in nutrient solution culture without or with Al at 148M and 222 M. The percent relative net root growth (% RNRG) and percent response were used to classify the populations into tolerant and sensitive to Al stress. In the field the parental lines, F1s and nine F2 segregating populations were grown in acid soil (pH 4.3) with high Al saturation (27%) without or with application of lime. The total number of leaves, plant height and seed yield per plant were evaluated. The F1s and some individual F2s performed better than the Al tolerantparent both in solution culture and under field conditions. Al tolerance was therefore successfully transferred into the Al sensitive variety. The superior progenies developed need to be advanced to a stable generation and released to sorghum farmers